EFL UNIVERSITY STUDENT ENGAGEMENT ON THE USE OF ONLINE DISCUSSION IN NORTH BALI - Anasthasia Carmanita Peu Ubu; I Nyoman Adi Jaya Putra; Made Hery Santosa (Language and Education Journal Undiksha, 2021)
This study aimed to investigate the university student engagement in the use of online discussions in English as a Foreign Language (EFL) Context in North Bali. Moreover, it was used to analyze university student limitations and supporting factors in the use of online discussions as part of blended-learning. The university student engagement was determined by Schlecthy’s theory of student engagement level. The result showed that the university student engagement in North Bali referred to the Ritual Compliance Level. They have low attention and no commitment in learning. They tend to learn dependently and work only for the sake of compliance. Besides, six factors were limited and five factors were supported them during the learning process through online discussion. Therefore, lecturers were suggested to create a pleasant learning atmosphere by building a good relationship with students in order to make students engaged in the online discussions.